Cypriot Journal of Educational Sciences (CJES) - Referees Index (Cypriot Journal of Educational Sciences, 2015)
Referees IndexThe academicians listed below have acted as referees since December 2015 for manuscripts in which the review process of which have been completed, as well as for those paper submissions which have been cancelled by the authors for some reason and for those that have been rejected. The editorial board members are grateful to all referees who have contributed to Cypriot Journal of Educational